Going "Straight to Basics": The Role of Lord Cooke in Reforming the Rule Against Hearsay - from Baker to the Evidence Act 2006 - McDonald, Elisabeth (Victoria University of Wellington Law Review, 2008)
In April of 1989, Cooke P, as he then was, proposed a test for the admissibility of oral hearsay (the fearful remarks of a woman later killed by her estranged husband) in a criminal trial. This common law admissibility test, focussing on the reliability of the statement (while implicitly acknowledging that the maker of the statement was not "available" to testify), was further developed in the Court of Appeal's decision in Bain (1996), and confirmed to have broad application in Manase (2001). The reliability and unavailability test has now become the admissibility test for hearsay evidence in the Evidence Act 2006. In this paper written in his honour, the author discusses the legacy of Lord Cooke in the 21st century liberalisation of the rule against hearsay.